Haemagogus leucocelaenus (Diptera: Culicidae), the potential wild vector of yellow fever in the border zone of northern Misiones, Argentina - Siches, Julieta Ailen (2021)
Haemagogus leucocelaenus (Diptera: Culicidae) is considered the primary vector of yellow fever virus (Flaviviridae) in wild environments in South America. Previous research has defined Hg. leucocelaenus as a wild species with phytotelmata-type breeding sites. The objective of this study was to report the temporal and space occurrence of Hg. leucocelaenus at the microscale in the wild-periurban fringe through a systematic and spatially stratified sampling using 81 ovitraps between April 2019 and February 2 020 in the locality of Puerto Iguazú, Argentina. Of the total ovitraps, eight were positive for Hg. leucocelaenus, six in the wild environment and two in the periurban environment. Regarding the time distribution, 98.5% of the occurrence was concentrated in November and December 2019 towards the beginning of the rainy season. The results confirm the habitat plasticity of Hg. leucocelaenus and establish the aptitude of artificial containers as a methodology in monitoring studies, since they illustrate the potential of wild populations to deposit fertile eggs in them at least up to 300 m from the wild-periurban fringe. This work is a contribution to determine the temporal and space risk of yellow fever virus transmission in the region, based on the distribution patterns of this species as a function to the ecotone associated with forest borders and climatic variables.